(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
For evaluating wave energy, wave energy period Te is commonly adopted. However, the in-charge government agencies in Taiwan traditionally provided with peak frequency Tp without giving information on the transferring relationship between Te and Tp. This results in difficulties on correctly evaluating wave energy potentials at certain marine waters. Thus, existing spectrum data need to be derived to calculate values of Tp and Te so as to derive representative transferring coefficient Cep for long-term evaluations on wave energy. This study aims at deriving values of Cep at relatively higher potential marine waters of Taiwan. As shown in Figure 1, the data were collected from two stations in Keelung marine waters and one station within marine waters for offshore wind of Changhua. By choosing different criteria for Cep, selected data were regressed for obtaining representative Cep in different seasons. For conservative point of views, the values of Cep ranging from 0.85 0.87 from data in northeaster monsoon months, as shown in Figure 2, being generally slightly smaller than those of the whole year, were adopted at the three stations. It is also found that the representative values of Cep were derived mainly from data comprising of exploitable wave power densities of between 2 80 kW/m2. Data collection instruments, selection criteria and associated outcomes shall be detailed in the full paper.